Crystal structure of human LDB1 in complex with SSBP2 - Wang, Hongyang (Proc Natl Acad Sci U S A, 2020)
The Lim domain binding proteins (LDB1 and LDB2 in human and Chip in Drosophila) play critical roles in cell fate decisions through partnership with multiple Lim-homeobox and Lim-only proteins in diverse developmental systems including cardiogenesis, neurogenesis, and hematopoiesis. In mammalian erythroid cells, LDB1 dimerization supports long-range connections between enhancers and genes involved in erythropoiesis, including the β-globin genes. Single-stranded DNA binding proteins (SSBPs) interact specifically with the LDB/Chip conserved domain (LCCD) of LDB proteins and stabilize LDBs by preventing their proteasomal degradation, thus promoting their functions in gene regulation. The structural basis for LDB1 self-interaction and interface with SSBPs is unclear. Here we report a crystal structure of the human LDB1/SSBP2 complex at 2.8-Å resolution. The LDB1 dimerization domain (DD) contains an N-terminal nuclear transport factor 2 (NTF2)-like subdomain and a small helix 4–helix 5 subdomain, which together form the LDB1 dimerization interface. The 2 LCCDs in the symmetric LDB1 dimer flank the core DDs, with each LCCD forming extensive interactions with an SSBP2 dimer. The conserved linker between LDB1 DD and LCCD covers a potential ligand-binding pocket of the LDB1 NTF2-like subdomain and may serve as a regulatory site for LDB1 structure and function. Our structural and biochemical data provide a much-anticipated structural basis for understanding how LDB1 and the LDB1/SSBP interactions form the structural core of diverse complexes mediating cell choice decisions and long-range enhancer–promoter interactions.